THE IMAGE OF DUKHEN IN CHINGIZ AITMATOV'S FIRST TEACHER'S WORK: THE PSYCHOLOGY OF THE ENLIGHTENMENT PERSONALITY (Educator Insights: Journal of Teaching Theory and Practice, 2026)
The article analyzes the image of Dushin in the story "The First Teacher" by Chingiz Aitmatov from the point of view of the psychology of the Enlightenment personality. The heroine's conflict with the spiritual world, inner beliefs, spiritual value and social environment is illuminated on the basis of psychological realism. As a result of the research, the image of Duchenne is interpreted as a symbol of enlightenment, selflessness and humanitarianism.